Response Spectrum Analysis for Regular Multistory Building by Using SAP 2000 - Supreem, K.; Venkata Gopi, B.; Jaya Sahithi, K.; Bhargav, G.; Sai Charan, S. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Earthquake is the most disastrous and unpredictable natural phenomenon which causes huge destruction to human lives as well as infrastructure. Seismic forces generated during earthquake loads to severe damage to structural elements and sometimes structural failure. Therefore, analysis and design of the building considering the effect of lateral forces is very important aspect. In the present study, a G+15 storied building was analyzed through the response spectrum analysis using SAP 2000 software. Response spectrum analysis (RSA) is a linear dynamic analysis method which measures the structural response to seismic events. The variation of acceleration, velocity and displacement responses with respect to change in period of the structure was identified, model load participating percentage and model mass participating factor.
Keywords: Response spectrum analysis; Sap2000; Residential building; Acceleration; velocity; displacement analysis